Aplicação foliar de cálcio, qualidade fisiológica, produtividade e resistência do tegumento das sementes de soja a danos mecânicos - Cabrera, Ingrid Cervo (2016)
The initial development of soybeans in Brazil was strongly supported by the development of technology that enabled the increased cultivation area, among which stands out the production of high quality seeds. We study and address the factors that contribute to maintaining a good vigor and germination in seeds produced increasingly necessary. Mechanical damage is one of the limiting factors to the production of soybeans. Because of mechanized activities during harvesting, processing, storage, transportation and planting operations, the seeds are subject to a number of injuries, reflecting the decrease in germination and vigor. Given the above, the objective of this study was to evaluate the efficiency of foliar application of Ca in reducing mechanical damage through the integument of the stamina and the physiological quality and productivity of soybean seeds. The seeds were submitted the following calcium foliar treatments: 1) 0.139 g of CaCl / 2 100 mL) 0.279 g of CaCl / 100 mL 3) CaCl 1,39g / 100ml 4) 2.79 g of CaCl / 100 ml 5 ) witness. After were made analysis of physiologic and mechanical damage, chemical analysis (Ca content) and productivity. The design used the field was randomized blocks and completely randomized design lab, the regression was done by Sisvar. Concludes program that the application of foliar calcium decreases the incidence of mechanical damage, as well as, improve seed quality and has a positive effect on yield components, however, varies depending on the soybean cultivar and calcium dose.